Neurological Complications after Coronary Artery Bypass Grafting for High-Risk Patients: Current State of the Problem - Gogayeva, O.; Rudenko, A.; Lazoryshynets, V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Neurological disorders are the most serious and debilitating complications of the postoperative period in cardiac surgery. The main clinical manifestations of cerebral dysfunction are as follows: stroke, decreased cognitive function, encephalopathy and depressive disorder. The aim. To perform a literature review of neurological complications after coronary artery bypass grafting (CABG) in high-risk patients. Results. The main neurological complications after CABG in high-risk patients were considered. The main pathophysiological mechanisms of development of cerebral circulation disorders in the form of macro- and microembolization, hypoperfusion secondary to hypotension and systemic inflammatory response have been determined. According to the literature, the incidence of stroke in the postoperative period is 1.5–6%, and it increases in the elderly. It’s important to perform carotid arteries ultrasound before CABG. According to the literature, carotid stenosis greater than 60% is found, depending on the age group, in 7–12% of patients. There is an ongoing debate around the world regarding the method and time of carotid atherosclerosis surgery (before revascularization, during or after CABG). Newman and co-authors have shown that in 5 years after myocardial revascularization, 41% of patients have a decrease in cognitive function, and it is lower than it was before surgery. Opponents of on-pump CABG have hypothesized the occurrence of Alzheimer’s disease after surgery with extracorporeal circulation, but authors from Mayo Clinic have investigated this question and refuted this theory; Canadian researchers have even proved the positive effect of revascularization on prevention of Alzheimer’s disease. The main strate gy for the prevention of cerebral complications is an individual approach for each high-risk patient.